The search of personified approach in the diagnostics of osteo-articular system changes in tuberculous spondylitis - S. V. Smerdin; Yu. A. Tsybulskaya; I. V. Shutikhina; R. V. Stavitsky; I. M. Lebedenko; L. S. Kokov; N. V. Selyukova (Сеченовский вестник, 2014)
Radiological methods are usually applied for the diagnosis of tuberculous spondylitis. Any of the imaging techniques (radiography, CT and MRI) has its own possibilities and limitations in the detection of this disease. Objective was to clarify the possibility of using a multislice linear tomography (digital tomosynthesis) of the spine and an automated classifi ed system of experimental scientific association in physics science and technology (ACS ESAPST) in detecting bone destructive changes in tuberculous spondylitis. The correlation was carried out between X-ray techniques (computed tomography and tomosynthesis and data obtained during treatment with ACS ESAPST. Tomosynthesis also allows to obtain a highly informative digital X-ray image and is almost comparable to CT for the detection of bone destructions in patients with tuberculous spondylitis. Tomosynthesis can replace computed tomography in some cases and provides many of the tomographic benefits (simplicity, speed, a reduced radiation dose and cost) in comparison with CT. In addition to the main radiology techniques, we found that using an automated classified system of experimental scientific association in physics, science and technology (ACS ESAPST) may help to detect tuberculous changes in the osteo-articular system.. ACS ESAPST can be used in patients with suspected development of a specific process in the osteo-articular system. An integrated approach in the diagnosis of tuberculous spondylitican be useful for diagnosis of bone tuberculosis at an early stage of the disease. And timely examination of this group of patients may prevent the development of irreversible complications.